2017
DOI: 10.1071/an16213
|View full text |Cite
|
Sign up to set email alerts
|

Identification of peptides in the terminal ileum of broiler chickens fed diets based on maize and soybean meal using proteomics

Abstract: A total of 160 Ross PM3 birds were used in a two treatment feeding study in order to explore the usefulness of proteomics to identify the origin of peptides in ileal digesta. Two diets were fed, one conventional maize/soy-based diet acted as a reference whereas a second diet, formulated to be nutritionally equivalent to the reference diet in protein and energy provision, contained 20% raw soy meal in order to (putatively) elicit changes in intestinal protein flow. Each diet was fed to 10 replicate cages of eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…A recent work ( Cowieson et al., 2016 ) used proteomics to explore the undigested peptides from the ileum of broilers fed with corn/SBM- or corn/SBM/raw SBM–based diets. In this work, it was observed that a substantial proportion of the protein in the ileum of broilers was from undigested SBM storage proteins (glycinin and beta-conglycinin) and endogenous proteins such as enzymes and mucin.…”
Section: Discussionmentioning
confidence: 99%
“…A recent work ( Cowieson et al., 2016 ) used proteomics to explore the undigested peptides from the ileum of broilers fed with corn/SBM- or corn/SBM/raw SBM–based diets. In this work, it was observed that a substantial proportion of the protein in the ileum of broilers was from undigested SBM storage proteins (glycinin and beta-conglycinin) and endogenous proteins such as enzymes and mucin.…”
Section: Discussionmentioning
confidence: 99%
“…However, digestion by endogenous protease is incomplete. Recent studies using proteomics approaches have revealed the presence of partially digested proteins from soybean meal (and other legume and cereal feed ingredients) in broiler digesta [2,3]. It is estimated that only about 80% of dietary soybean meal is digested by swine and poultry [4,5] or even less in high fiber, high phytate diets such as those containing industrial by-products [6,7].…”
Section: Introductionmentioning
confidence: 99%